Experimenting the aplicability of support vector machine regression in rainfall prediction [compact disc] - 217584 Junaida Sulaiman (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2005